Access to Language Training and Local Integration of Refugees - Mette Foged; Cynthia van der Werf (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
This paper examines whether proximity to language classes raises refugees' language proficiency and improves their social and economic integration. Our identification strategy leverages the opening, closing and gradual expansion of local language training centers in Denmark, as well as the quasi-random assignment of the refugees to locations with varying proximity to a language training center. First, we show that refugees' distance from the assigned language training center is as good as random. Second, we show that language skills decrease monotonically with commuting time such that a one-hour decrease in commuting time increases fluency in the Danish language by 4 to 6 percent relative to the sample mean. The exogenous variation in language proficiency generates substantial positive effects on post language training human capital acquisition and on the integration of the refugees in the local communities where they were initially placed, as measured by the lower exit rates from those same communities and lower mobility to the largest, most immigrant-dense, cities in Denmark.
Keywords: J24; J60; 330; refugee integration; language skills